Glutathione and nitrite levels in induced sputum at COPD patients and healthy smokers - Turgut, Teyfik; İlhan, Nevin; Deveci, Figen; Akpolat, Nusret; Erden, Ersin Şükrü; Muz, M. Hamdi (Journal of Thoracic Disease, 2014)
Objectives: The role of oxidative stress at the pathogenesis of chronic obstructive pulmonary disease (COPD) is known. The aim of this study is to investigate the oxidative stress with sputum induction that is a simple method in COPD patients and healthy smokers. Methods: Sputum induction was performed in 21 COPD patients (10 stable, 11 acute exacerbations), nine healthy smokers, and ten healthy non-smokers. Glutathione, NO2– levels, and cell counts at sputum, and plasma NO2– contents were evaluated in all subjects. Results: Mean sputum glutathione and NO2– levels were significantly higher in acute exacerbations with COPD patients than healthy smokers (P=0.007 and P